Enhancement of dispersion optical parameters of Al2O3/ZnO thin films fabricated by ALD. (15th July 2020) - Zaka, Hanaa; Fouad, S.S.; Parditka, B.; Bekheet, A.E.; Atyia, H.E.; Medhat, M.; Erdélyi, Z.
Highlights: The correlation between the deposition parameters and of pure and mixed Inlayers thin film samples. The value of the optical band gap was found to increase from bilayered to trilayered. The phase velocity, electric susceptibility, reflection loss, and dispersion of linear and nonlinear parameters are presented. The refractive index is discussed in terms of the single oscillator model proposed by Wemple – DiDomenico. Abstract: Thin film properties are extremely sensitive to the film preparation conditions, thus our research is dedicated to establish the correlation between the deposition parameters and properties in Al2 O3 /ZnO bilayered and Al2 O3 /Al2 O3 -ZnO mixed oxide/ZnO trilayred thin film samples prepared by atomic layer deposition (ALD) technique with the same total thickness and the thickness ratio of the pure Al2 O3 and ZnO layers. The extracted results from the X-ray diffraction suggested structural transformation as a function of the number of layers of pure and mixed Al2 O3 /ZnO. Analysis was performed to investigate the physical, optical and nonlinear optical properties. The dispersion parameters were investigated in the wavelength range of 280 – 2500 nm. The absorption coefficient, optical, electrical and thermal conductivities, furthermore penetration depth have also been determined. The absorption mechanism of the prepared samples obeys the rule of allowed indirect optical transitions. The value of the optical band gap was found to increase from 3.205 eV for bilayered to 3.229 eV for trilayered samples. The dispersion of the refractive index is described and discussed in terms of the single oscillator model proposed by Wemple – DiDomenico. Moreover, the phase velocity, electric susceptibility, reflectionloss, and dispersion of nonlinear parameters such as third order nonlinear optical susceptibility and nonlinear refractive index are presented. All the studied properties and determined parameters allowing us to indicate clearly the effect of the difference between Al2 O3 /ZnO bilayered and Al2 O3 /Al2 O3 -ZnO mixed oxide/ZnO trilayered thin films, and how the optical properties of thin films could be enhanced and improved by changing only the stacking of Al2 O3 and ZnO layers. Overall, on the basis of these results several applications could be suggested for the layer samples obtained in this work.